School committee composition: Exploring the role of parental and female representation in India - GUHA, Panchali (Institutional Knowledge at Singapore Management University, 2023)
Motivation: The adoption of school-based management (SBM) reforms has led to the formation of local-level school committees in many low- and middle-income countries. These committees are usually created with the stated aim of giving parents or local community members a greater say in school management. Various studies have, however, highlighted difficulties with parental and female participation, casting doubt on the extent to which greater community representation improves school management. Purpose: The article examines empirically whether greater parental and female representation in Indian school management committees (SMCs) is associated with school improvement as measured by increases in the school-level provision of basic infrastructure and services. Methods and approach: Fixed-effects regression models are estimated using school-level panel data. Findings: I find that increased parental representation is not associated with improvements in school infrastructure/service provision. Rather, what contributes strongly to improved outcomes is increased representation of elected local authority members. Overall, schools with female-majority SMCs also perform better. Policy implications: While the requirement for Indian SMCs to include representation from local government appears to be an effective feature of their composition, there is a need for capacity-building efforts to ensure that parent members also contribute effectively to school management. SMCs should also be encouraged to meet the female representation quota, as the analysis suggests a positive association between female representation and school outcomes.